Syndecan-4 enhances PDGF-BB activity in diabetic wound healing. (15th September 2016) - Das, Subhamoy; Majid, Marjan; Baker, Aaron B.
Graphical abstract: Abstract: Non-healing ulcers are a common consequence of long-term diabetes and severe peripheral vascular disease. These non-healing wounds are a major source of morbidity in patients with diabetes and place a heavy financial burden on the healthcare system. Growth factor therapies are an attractive strategy for enhancing wound closure in non-healing wounds but have only achieved mixed results in clinical trials. Platelet derived growth factor-BB (PDGF-BB) is the only currently approved growth factor therapy for non-healing wounds. However, PDGF-BB therapy is not effective in many patients and requires high doses that increase the potential for side effects. In this work, we demonstrate that syndecan-4 delivered in a proteoliposomal formulation enhances PDGF-BB activity in diabetic wound healing. In particular, syndecan-4 proteoliposomes enhance the migration of keratinocytes derived from patients with diabetes. In addition, syndecan-4 proteoliposomes sensitize keratinocytes to PDGF-BB stimulation, enhancing the intracellular signaling response to PDGF-BB. We further demonstrated that co-therapy with syndecan-4 proteoliposomes enhanced wound closure in diabetic, hyperlipidemic ob/ob mice. Wounds treated with both syndecan-4 proteoliposomes and PDGF-BB had increased re-epithelization and angiogenesis in comparison to wounds treated with PDGF-BB alone. Moreover, the wounds treated with syndecan-4 proteoliposomes and PDGF-BB also had increased M2 macrophages and reduced M1 macrophages, suggesting syndecan-4 delivery induces immunomodulation within the healing wounds. Together our findings support that syndecan-4 proteoliposomes markedly improve PDGF-BB efficacy for wound healing and may be useful in enhancing treatments for non-healing wounds. Statement of Significance: Non-healing wounds are major healthcare issue for patients with diabetes and peripheral vascular disease. Growth factor therapies have potential for healing chronic wounds but have not been effective for many patients. PDGF-BB is currently the only approved growth factor for enhancing wound healing. However, it has not seen widespread adoption due to limited efficacy and high cost. In this work, we have developed an enhancing agent that improves the activity of PDGF-BB in promoting wound healing in animals with diabetes. This co-therapy may be useful in improving the efficacy of PDGFBB and enhance its safety through lowering the dose of growth factor needed to improve wound healing.